El territorio cuadriculado. La adaptación de un modelo territorial estadounidense en Argentina, 1850-1890 - Melina Yuln (Nuevo mundo - Mundos Nuevos, 2012)
This article intends to show the influence of the North American territorial model, which was defined by the end of the eighteenth century, exercised in the organization of the argentine territory during the second half of the nineteenth century. This study starts by the configuration of a regular territorial grid that applied over public land in both study cases. In Argentina converge transplanted legal frameworks, colonial heritage and experiments driven by the ideas of the Bourbon Enlightenment during the early nineteenth century. Through an iconographic perspective this paper will try to show that it is possible to deepen the analysis of the legal regulation of public land - partly inherited and partly readapted of imported models- and establish the degree of influence in the definition of a particular territorial shape.